Pengaruh Faktor Keuangan dan Non Keuangan pada Keberhasilan UMKM di Kota Bandar Lampung - Nurmala Nurmala; Damayanti Damayanti; Evi Yuniarti (Politeknik Negeri Lampung, 2019)
This study aims to analyze the influence of financial and non-financial factors on the success of SMEs in Bandar Lampung city. Financial factors considered as the indicators of success are profitability, liquidity and sales. Non-financial factors that become indicators are operational, entrepreneurial characteristics, company characteristics, conceptual variables, and entrepreneurial behavior. Of the 208 SMEs that were given questionnaires and asked for their financial statements, after reviewing the complete answers to the questionnaire and the availability of financial reports, 96 SMEs could be processed. The correlation and regression tests were carried out after the validity and reliability were tested. The results obtained indicate that the level of relationship between the two variables is strong. Based on the results of calculations and discussions, financial and non-financial factors have a significant influence on the success of SMEs in Bandar Lampung city, especially in Rajabasa and Kedaton.Keywords: Influence, Finance, Non-Finance, UMKM, and Bandar Lampung